Comparative transcriptomics of porcine liver-resident CD8αdim, liver CD8αhigh and circulating blood CD8αhigh NK cells reveals an intermediate phenotype of liver CD8αhigh NK cells - Hermans, Leen; Denaeghel, Sofie; Jansens, Robert J. J.; De Pelsmaeker, Steffi; Van Nieuwerburgh, Filip; Deforce, Dieter; Hegewisch-Solloa, Everardo; Mace, Emily M.; Cox, Eric; Devriendt, Bert; Favoreel, Herman W. (Frontiers in Immunology, 2023)
Liver-resident NK (lrNK) cells have been studied in humans as well as in mice. Unfortunately, important differences have been observed between murine and human lrNK cells, complicating the extrapolation of data obtained in mice to man. We previously described two NK cell subsets in the porcine liver: A CD8αhigh subset, with a phenotype much like conventional CD8αhigh NK cells found in the peripheral blood, and a specific liver-resident CD8αdim subset which phenotypically strongly resembles human lrNK cells. These data suggest that the pig might be an attractive model for studying lrNK cell biology. In the current study, we used RNA-seq to compare the transcriptome of three porcine NK cell populations: Conventional CD8αhigh NK cells from peripheral blood (cNK cells), CD8αhigh NK cells isolated from the liver, and the liver-specific CD8αdim NK cells. We found that highly expressed transcripts in the CD8αdim lrNK cell population mainly include genes associated with the (adaptive) immune response, whereas transcripts associated with cell migration and extravasation are much less expressed in this subset compared to cNK cells. Overall, our data indicate that CD8αdim lrNK cells show an immature and anti-inflammatory phenotype. Interestingly, we also observed that the CD8αhigh NK cell population that is present in the liver appears to represent a population with an intermediate phenotype. Indeed, while the transcriptome of these cells largely overlaps with that of cNK cells, they also express transcripts associated with liver residency, in particular CXCR6. The current, in-depth characterization of the transcriptome of porcine liver NK cell populations provides a basis to use the pig model for research into liver-resident NK cells.